2010
DOI: 10.1093/pcp/pcq127
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Arabidopsis ATSIP2 (At3g57520) as an Alkaline  -Galactosidase with a Substrate Specificity for Raffinose and an Apparent Sink-Specific Expression Pattern

Abstract: Arabidopsis ATSIP2 has recently been suggested to be a raffinose synthase gene. However, it has high amino acid identity to functionally characterized alkaline α-galactosidases from Cucumis melo and Zea mays. Using the Sf9 insect cell expression system, we demonstrate that recombinant ATSIP2 is a genuine alkaline α-galactosidase with a distinct substrate specificity for raffinose, and not a raffinose synthase. A β-glucuronidase reporter construct using the ATSIP2 promoter shows that ATSIP2 is strongly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 18 publications
(24 reference statements)
0
57
0
Order By: Relevance
“…3.2.1.22,) was discovered from the reverse library. Alkaline α-galactosidase hydrolyzes a variety of α-galactose-containing saccharides, in particular raffinose (Gao and Schaffer, 1999;Peters et al, 2010). In our work, the gene was shown to be down-regulated by low temperature, which indicates that the decomposition of raffinose might be arrested.…”
Section: Discussionmentioning
confidence: 52%
“…3.2.1.22,) was discovered from the reverse library. Alkaline α-galactosidase hydrolyzes a variety of α-galactose-containing saccharides, in particular raffinose (Gao and Schaffer, 1999;Peters et al, 2010). In our work, the gene was shown to be down-regulated by low temperature, which indicates that the decomposition of raffinose might be arrested.…”
Section: Discussionmentioning
confidence: 52%
“…Cell wall modifications are important to control cell expansion in response to drought (Wu and Cosgrove, 2000;Moore et al, 2008;Minic et al, 2004), and genes encoding cell wall modifiers have previously been shown to be differentially expressed in response to mild drought in growing leaves (Harb et al, 2010;Clauw et al, 2015). Two other proteins encoded by core genes that regulate osmolyte concentrations were found to be up-and downregulated, respectively: D-1-PYRROLINE-5-CARBOXYLATE SYNTHASE1 (P5CS1) is the rate-limiting enzyme in proline biosynthesis, a wellknown osmoprotectant (Strizhov et al, 1997;Szabados and Savouré, 2010), and SMALL AND BASIC INTRINSIC PROTEIN2 (SIP2) is suggested to be involved in phloem unloading of raffinose in sink leaves (Peters et al, 2010). Raffinose and other members of the raffinose family oligosaccharides are involved in stress tolerance and act as antioxidants.…”
Section: Predictive Genes For Mild Drought In Growing Leavesmentioning
confidence: 99%
“…In order to obtain stably transformed Arabidopsis plants (T3 homogenous lines), the binary expression vector pCHF1301 and pCHF3301 carrying a GUS reporter gene driven by the CaMV35S promoter were transformed into A. thaliana (Col-0) by the floral dip method, and positive transformants were selected on MS medium containing 25 mg/L hygromycin (Hyg) B, and by spraying Basta under controlled environmental conditions as described previously, respectively (Zhang et al, 2006;Peters et al, 2010). All of the Arabidopsis transformants were characterized by PCR with primers Hyg-F and Hyg-R, and Bar-F and Bar-R, respectively.…”
Section: Gus and Gfp Assaysmentioning
confidence: 99%